2018
DOI: 10.37940/ajvs.2018.11.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the arginine on some blood and biochemical parameters of Awassi Ewes

Abstract: This study was carried out in The Ruminant Research Station (Abu Ghraib)/ Department of Animal Resources Research/ Office of Agricultural Research/ Ministry of Agriculture during the period from July 6, 2017 to Feb 3, 2018. Twenty one non pregnant Awassi Turkish ewes were used in the experiment. The age of the animals ranged between 2-5 years old with a weight ranged between 45-70kg. Befor insert CIDR, The animals were examined with ultrasonography to be sure that they were not pregnant. These ewes were divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…It is also in agreement with the report of Greyling (2000) and Enginler et al (2017) whom stated that complete uterine involution in slaughtered animals is 28 days, the mean involution period in single and twin saturated does to be 27.10±0.43 and 28.29±0.54 days respectively, and complete uterine involution in goats occurred within 28 days postpartum. The current study is also in close agreement with previous reports (Baru et al, 1983;Tian and Noakes, 1991;Sanchez et al, 2002;Ababneh and Degefa, 2005;Takayama et al, 2010;Zongo et al, 2014;Medan and El-Daek, 2015) but is in contrast with the report of others (Rubianes et al, 1996;Zdunczyk et al, 2004;Fernandes et al, 2013;Fasulkov, 2014;Ahmed et al, 2016;Souhayla et al, 2016) who observed the end of uterine involution after 30 days. Shorter days postpartum (16 days) period was also reported by Sanchez et al (2002)…”
Section: Discussionsupporting
confidence: 93%
“…It is also in agreement with the report of Greyling (2000) and Enginler et al (2017) whom stated that complete uterine involution in slaughtered animals is 28 days, the mean involution period in single and twin saturated does to be 27.10±0.43 and 28.29±0.54 days respectively, and complete uterine involution in goats occurred within 28 days postpartum. The current study is also in close agreement with previous reports (Baru et al, 1983;Tian and Noakes, 1991;Sanchez et al, 2002;Ababneh and Degefa, 2005;Takayama et al, 2010;Zongo et al, 2014;Medan and El-Daek, 2015) but is in contrast with the report of others (Rubianes et al, 1996;Zdunczyk et al, 2004;Fernandes et al, 2013;Fasulkov, 2014;Ahmed et al, 2016;Souhayla et al, 2016) who observed the end of uterine involution after 30 days. Shorter days postpartum (16 days) period was also reported by Sanchez et al (2002)…”
Section: Discussionsupporting
confidence: 93%
“…In a study, the effect of prostaglandins (PGF2α) and oxytocin on postpartum uterine involution of Awassi ewes were evaluated (3) which the postpartum gravid horn diameter was found as 6.50±0.45 and 6.45±0.25 in the PGF2α and oxytocin groups, respectively, on the 7 th day after parturition. On the 21 st day of pp, Ahmed et al (3) found the diameter to be 2.92±0.43 and 3.45±0.13 in the PGF2α and oxytocin groups, respectively. The pp gravid horn diameter decreased more rapidly in the current study than in Ahmed et al's (3) study.…”
Section: Discussionmentioning
confidence: 97%
“…There are very few reports on postpartum uterine involution in small ruminants, and most of them focus on postmortem evaluations (11,17,22); moreover, the previous studies on the postpartum uterus were mostly performed only by B-mode USG (1,3,18,38). This study was designed to investigate, by pulsed-wave Doppler sonography, the involution of the sheep uterus in the postpartum period following the delivery of medications that contract the uterus.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental rats were euthanized and a full necropsy was performed to detect any abnormalities and gross changes in liver and spleen that dissected after that 1c.m³ from organs were taken then fixed in 10% neutral buffered formalin for (2-3) days, then routinely processed in histokinette (ATP-1000\HESTION), tissue sections were embedded in paraffin (Eman et al, 2016) after that paraffin blocks with implanted tissue slices were sectioned at 5 µm thickness by microtome) (Yidi) (Ahmed and Bushra, 2013), and staining by routine hematoxylin and eosin stain then examined under light microscope(Olympus) according to (Steven and Bancroft, 1997).…”
Section: Histopathological Examinationmentioning
confidence: 99%